PENERAPAN TEKNIK PENGGAMBARAN GARIS KONTUR MENGGUNAKAN AUTO CAD 3D - Novatus Senduk (Jurnal Teknik Sipil Terapan, 2022)
In applying engineering drawings for bridge construction, a contour line drawing section provides elevation data from the average sea level. It is drawn at equal intervals to create a topographic map. Nowadays, technology is increasingly advanced. In every field of work, computers are used as tools that help make work easier. One of the tools that help facilitate work in computers is C.A.D (Computer-Aided Design) or Computer Assisted Design, which aims to make it easier for designers and drafters to express their ideas visually in the appearance of image objects. With this research, understanding, and steps to draw contour lines using AutoCAD software are obtained, then visualize it into a simple form in 3 dimensions, calculate the drawing volume, and find out the obstacles in applying contour line drawing. This research was conducted for eight months. The research method used is a practical in terms of its place, namely research conducted in a laboratory, and a computer laboratory/drawing laboratory that provide computer facilities. The research results to draw contour lines that are fast and practical using Auto CAD 3D, which shows accurate 3-dimensional image visualization.